Investigation of an interleukin-4 promoter polymorphism for associations with asthma and atopy. Issue 8 (August 1996) - Walley, A J; Cookson, W O
Abstract : The cytokine cluster located on chromosome 5 has been shown by linkage studies to play a role in the genetic determination of circulating immunoglobulin E (IgE) levels in atopic subjects. In the study presented here, the reported chromosome 5 linkage has been investigated in two sets of subjects. The first consisted of a general population sample of 230 nuclear families (n = 1004) from Busselton, a small West Australian country town. The second group consisted of 124 unrelated atopic asthmatics and 59 unrelated non-atopic, non-asthmatic controls, all resident in the Oxfordshire Regional Health Authority area in the United Kingdom. A previously reported interleukin-4 (II-4) promoter polymorphism (-590 C-->T) was analysed in these populations by a newly designed method of specific PCR amplification and BsmFI restriction endonuclease digestion. In the Busselton population the polymorphism was shown to be weakly associated with specific IgE to house dust mite (Mann-Whitney-U test, p = 0.013) and to wheeze (MWU test, p = 0.029), but not with specific IgE to grass pollen, total serum IgE, bronchial hyperresponsiveness, eosinophil count, or asthma. In the Oxfordshire subjects there were no statistically significant associations with any measure of asthma or atopy. These data show that the -590 C-->T II-4 promoter polymorphism is only weakly associated with certain measures of asthma and atopy in some subjects. It was specifically not associated with serum IgE concentration or asthma in either of the two groups in this study.